(untitled) - Graham, Gavin (Hoboken, NJ., 2014)
Colombia, Indonesia, Vietnam, Egypt, Turkey, and South Africa (CIVETS) are six countries poised to be the next group of developing nations to see an economic boom. These countries, similar to the BRIC (Brazil, Russia, India, and China) are currently reaping the rewards of a growing economy.
Keywords: Investments, Foreign,Đầu tư nước ngoài; Developing countries,Các nước đang phát triển